Oxytocin Secretion Is Related to Measures of Energy Homeostasis in Young Amenorrheic Athletes - Lawson, Elizabeth A. (Endocrine Society, 2014)
CONTEXT: Oxytocin has been implicated in the modulation of energy metabolism in animals. Oxytocin knockout mice develop obesity without a change in food intake, suggesting that a lack of oxytocin may reduce metabolic rate. Furthermore, administration of oxytocin centrally reduces food intake in rats, an effect reversed by an oxytocin antagonist, implying that oxytocin may regulate appetite and energy intake. We have previously demonstrated that young female athletes (in a higher energy expenditure state than nonathletes) have low nocturnal oxytocin compared with nonathletes. Whether oxytocin is associated with measures of energy homeostasis in athletes is unknown. OBJECTIVE: We hypothesized that oxytocin, a signal for energy availability, would be associated with other measures of energy homeostasis in young female athletes. DESIGN AND SETTING: We performed a cross-sectional study of 45 females, aged 14–21 years [15 amenorrheic athletes (AA), 15 eumenorrheic athletes, and 15 nonathletes] of comparable body mass index. METHODS: Dual x-ray absorptiometry was performed to assess body composition. Indirect calorimetry was used to measure resting energy expenditure (REE). Fasting levels of oxytocin, energy homeostasis hormones irisin and fibroblast growth factor-21, and appetite-regulating hormone peptide YY were obtained. RESULTS: In AA, oxytocin secretion was positively correlated with surrogate measures of energy availability, including weight (r = 0.65, P = .009) and body mass index (r = 0.61, P = .016). Furthermore, oxytocin was associated with REE (r = 0.80, P = .0003), independent of lean mass, and with irisin (r = 0.74, P = .002) and fibroblast growth factor-21 (r = 0.58, P = .024). In eumenorrheic athletes, oxytocin was associated with REE (r = 0.59, P = .021), independent of lean mass. In nonathletes, oxytocin secretion was not significantly associated with measures of energy homeostasis. CONCLUSIONS: In AA, oxytocin secretion is associated with measures of energy availability and expenditure, suggesting that oxytocin may be involved in regulation of energy balance in energy deficient states. Further studies determining the role of oxytocin in appetite and energy homeostasis in athletes are warranted.